Preissmann Four-Point Methods for Solution of Simplified Saint-Venant Equations Applied to Flood Routing in Prismatic Open Channels - Bambang Agus Sulistyono; Widodo, Suryo (Science and Technology Indonesia, 2024)
This research goal to compare the flow properties in the rectangular and trapezoidal open channels by examining the influence of the channel side slope is depicted by simplified Saint Venant Equations. The solution of these equations has been completed numerically by using Preissmann four-point scheme. The model is simulated using the Matlab application to point out the flow properties. The proposed model is validated by the model without simplification which was selected from the literature. The validation outcomes indicate that in common, the simulation outcomes of the two models have a good agreement. The simulation results show that the greater the slope of the channel side, the greater the peak discharge and the greater the time shift. The analysis emphasizes how channel geometry influences flow behavior, indicating that trapezoidal channels, with inclined side slopes z, yield slightly higher peak discharges compared to rectangular ones. For z = 0, discharge of peak Q = 7.38 m3/s and t = 18 s. For z = 2, discharge of peak Q = 7.39 m3/s and t = 21 s. For z = 4, discharge of peak Q = 7.45 m3/s and t = 23 s. For z = 6, discharge of peak Q = 7.51 m3/s and t = 24 s.